Multifunctional Nanocarriers‐Mediated Synergistic Combination of Immune Checkpoint Inhibitor Cancer Immunotherapy and Interventional Oncology Therapy. Issue 10 (2nd August 2021) - Choi, Bongseo; Kim, Dong-Hyun
Abstract : Immune checkpoint inhibitor (ICI) cancer immunotherapies are becoming one of the standard therapies for cancer patients. However, ICI cancer immunotherapy's overall response rate is still moderate and even combinational ICI cancer immunotherapies are not showing significant improvement in therapeutic outcomes. Only a subset of patients respond to the therapy due to the resistance and ignorance to the ICI cancer immunotherapy. Following immune‐related adverse events (irAEs) is also limiting the whole therapeutic regimen. New approaches that can increase the immunotherapeutic efficacy and reduce systemic irAEs are required. Recently, multifunctional nanocarriers, which can extend the half‐life of ICIs and modulate tumor microenvironment (TME), have shown a substantial opportunity to enhance ICI cancer immunotherapies. Interventional oncology (IO), allowing simultaneous diagnosis, immunogenic locoregional therapeutic delivery, and real‐time monitoring of the treatment efficacy, has advanced to demonstrate the effective conversion of TME. The use of multifunctional nanocarriers with the IO therapies amplifies the image guidance capability and immunogenic therapeutic localization for the potential combinational ICI cancer immunotherapy. Herein, emerging opportunity of multifunctional nanocarriers‐mediated synergistic combination of ICI cancer immunotherapy and IO local therapy is discussed. Abstract : Herein, an overview of the current and future application of multifunctional nanocarriers‐mediated synergistic combination of interventional oncology (IO) therapy and immune checkpoint inhibitor (ICI) cancer immunotherapy is given.